Bone turnover in pregnancy, measured by urinary CTX, is influenced by vitamin D supplementation and is associated with maternal bone health: findings from the Maternal Vitamin D Osteoporosis Study (MAVIDOS) trial. Issue 5 (23rd July 2021) - Curtis, Elizabeth M; Parsons, Camille; Maslin, Kate; D'Angelo, Stefania; Moon, Rebecca J; Crozier, Sarah R; Gossiel, Fatma; Bishop, Nicholas J; Kennedy, Stephen H; Papageorghiou, Aris T; Fraser, Robert; Gandhi, Saurabh V; et al.
ABSTRACT: Background: The pattern of change in maternal bone turnover throughout pregnancy is poorly characterized. Objectives: We investigated changes across pregnancy in a marker of maternal bone resorption, urinary C-terminal telopeptide of type I collagen (CTX), the influence of gestational vitamin D supplementation, and associations between CTX and maternal postnatal bone indices. Methods: MAVIDOS (the Maternal Vitamin D Osteoporosis Study) is a randomized, double-blind, placebo-controlled trial of 1000 IU cholecalciferol/d compared with placebo from 14 weeks of gestation to birth. Maternal second-void urinary α- and β-CTX were measured (ELISA) at 14 and 34 weeks of gestation; DXA was performed within 2 wk postpartum. The Mann–Whitney Rank Sum test, Spearman's rank correlation, and linear regression were used to compare median CTX values within and between groups from early to late pregnancy, and associations with maternal bone outcomes. Results: In total, 372 women had CTX and 25-hydroxyvitamin D [25(OH)D] measured in early and late pregnancy. CTX at 14 and 34 weeks of gestation were correlated in both placebo ( r = 0.31) and cholecalciferol ( r = 0.45) groups ( P < 0.0001). Median CTX increased from 14 to 34 weeks of gestation in both groups ( n = 372 total) [placebo ( n = 188): from 223.6 to 449.7 μg/mmol creatinine; cholecalciferol ( n = 184): from 222.3 to 419.3 μg/mmol creatinine; P = 0.03 for placebo compared with cholecalciferol difference in CTX at 34 weeks of gestation]. The conditional mean ± SD increase in CTX [z-score (SD)] from early to late pregnancy was greater in the placebo group ( n = 188) than in the cholecalciferol group ( n = 184) (placebo: 0.16 ± 0.92; cholecalciferol: −0.16 ± 1.06; P -difference < 0.01). Higher CTX at 34 weeks of gestation was associated, similarly in both groups, with lower maternal total hip and lumbar spine bone mineral content and bone mineral density (BMD) (e.g., lumbar spine BMD: β = −0.02 g · cm −2 · SD −1 increase in CTX; 95% CI: −0.027, −0.002 g · cm −2 · SD −1 ; P = 0.02, n = 283). Conclusions: Maternal urinary CTX, a bone resorption marker, rises through pregnancy, although to a lesser degree with gestational cholecalciferol supplementation, and is inversely associated with maternal bone mass postpartum. This trial was registered at www.isrctn.com as ISRCTN 82927713 and eudract.ema.europa.eu as EudraCT 2007-001716-23.